PROBLEMS AND FACTORS INFLUENCING THE USE OF THE INTERNET IN LEARNING LISTENING AMONG FIRST YEAR MAINSTREAM STUDENTS AT THE FACULTY OF ENGLISH TEACHER EDUCATION, ULIS, VNU - Lương, Thúy Nguyệt (2020)
The increasing use of the Internet among students urges the importance of exploring the factors that might influence the effective exploitation of the information technology in language learning. Particularly, among four skills, listening is the one that can benefit significantly from the technology advancement. As the result, this research attempts to framework the problems and factors affecting the use of the Internet in learning listening among first year mainstream students within the context of Faculty of English Language Education, University of Language and International Studies, Vietnam National University. The data were collected by means of survey questionnaire and interview. Results showed that the use of the Internet among the target population were affected by both objective factors namely facility, health, finance, oral text language, technique related ones, and subjective factors including habit, belief and the computer and Internet skill. The findings from the study hopefully will benefit students by raising their awareness of the determinants impacting their application of the modern technology to their listening learning. Moreover, by providing the real situation of students’ difficulties, the teachers and policy makers are expected to make necessary changes in the curriculum for better learning and teaching quality.